Combination effects of a fatty diet and exercise on the depressive state and cardioprotection in apolipoprotein E knockout mice with a change in RCAN1 expression. Issue 11 (November 2020) - Shuo, Wang; Li, Haicong; Muneko, Nishijo; Yoshikazu, Nishino; Kato, Nobuo; Kasamaki, Yuji; Ueda, Tadashi; Kanda, Tsugiyasu
Objective: Regulator of calcineurin 1 (RCAN1) controls plasticity of the nervous system and depressive conditions by regulating brain-derived neurotropic factor (BDNF) and plays a crucial role in neural and cardiac pathways. The apolipoprotein E gene ( ApoE ) is a robust risk factor for progression of Alzheimer's disease. A fatty diet is considered detrimental for metabolic disorders, such as obesity and cardiovascular diseases. Methods: We examined the neuronal and cardiac protective roles of RCAN1 in ApoE−/− mice that were fed a high- or low-fat diet with and without voluntary movement for 3 months. Organ weights, laboratory data, histology, RNA expression, and behavior were examined. Results: A high-fat diet with exercise improved depressive function, as examined by the forced swimming test, and RCAN1 mRNA expression was induced in the hippocampus. A low-fat diet with exercise resulted in a reduced body weight, higher heart weight/body weight ratio, and lower circulating triglyceride levels compared with a low-fat diet without exercise. RCAN1 mRNA expression was increased in cardiomyocytes in ApoE−/− mice. Conclusions: The combination of a high-fat diet and exercise might reduce depressive function, whereas a low-fat diet with exercise leads to cardioprotection. Induction of RCAN1 expression might affect neuroplasticity and cardiac function.